Male SIRT1 insufficiency leads to sperm with decreased ability to hyperactivate and fertilize - Iniesta-Cuerda, María; Havránková, Jiřina; Řimnáčová, Hedvika; García-Álvarez, Olga; Nevoral, Jan (Reproduction in domestic animals, 2022)
Deficient sperm motility is a frequent cause of the age-related male sub-/infertility. Since the protein sirtuin 1 (SIRT1) develops anti-aging action and participates in sperm motility and ATP synthesis in mitochondria, we investigated its role in the acquisition of hyperactivated motility during capacitation. For this, the dynamics of sperm subpopulations were studied, using males of Sirt1+/- heterozygous mutant mice. After 2 hr of capacitation, we observed reduced percentage of hyperactivated spermatozoa in Sirt1+/- males. Interestingly, prior to capacitation, Sirt1+/- spermatozoa showed higher mitochondrial superoxide levels, which could render mitochondrial injury and thereby motility defects. Accordingly, the fertilization rate of Sirt1+/- males after mating was decreased. We elucidated that SIRT1 male insufficiency underlies posterior sperm defects to hyperactivate during capacitation and propose Sirt1+/- males as a model for the study of the age-related infertility.
Keywords: sperma; Sirtuin 1; hyperactivated motility; adenosintrifosfát; spermie; superoxidy; mužská infertilita; SIRT1; Sperm Motility; Superoxides; sperm capacitation; fertilizace; Sperm Capacitation; zvířata; myši; Mice; Fertilization; Adenosine Triphosphate; motilita spermií; Male; Infertility, Male; Semen; Spermatozoa; Animals; kapacitace spermií; mužské pohlaví; sirtuin 1; infertility